Surgical proficiency grading and outcome of fistula repair; does it really matter? - Lawal, OO; Morhason-Bello, IO; Bello, OO; Abduls-Salam, RA; Efem, I; Amodu, A; Ojengbede, AO (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To measure and validate the outcome of fistula repair with FIGO surgical proficiency grading. Methods: Review of obstetric fistula managed at University College Hospital/Adeoyo fistula center was done. The lead expert fistula surgeon trainer at FIGO certified fistula training center graded all trainee surgeons and fistula complexity. Data was collected using a structured proforma. The fistula characteristics,level of surgeon and surgical outcomes were assessed. Analysis was done using SPSS version 25. Level of significance was set at P<0.05. Results: Out of the 216 fistulas reviewed, 86 (47.5%) were classified as complex fistula, 43 (23.8%) as simple, moderate 38(21%) and irreparable 14 (7.7%). Majority 146 (67.3%) were performed by advanced level surgeons and only 9 (4.1%) by standard level surgeons. Successful outcome for all levels was above 80% (Standard = 88.9%, Advanced = 81.4% and Expert=83.9%). Expectedly, surgeons at the expert level had a higher closure for complex fistula 86% vs 64.3% compared to advanced level. Conclusions: This preliminary study shows some sort of validation of the FIGO grading system with a high successful outcome of repair across all proficiency levels.